Influence of the Metal Ion on the Electrocatalytic Hydrogen Production by a Thiosemicarbazone Palladium Complex. Issue 20 (6th May 2018) - Straistari, Tatiana; Hardré, Renaud; Massin, Julien; Attolini, Mireille; Faure, Bruno; Giorgi, Michel; Réglier, Marius; Orio, Maylis
Abstract : We describe the synthesis and characterization of a new mononuclear palladium complex (PdL ) based on a thiosemicarbazone ligand. X‐ray diffraction data collected on single crystals reveal that the complex is a neutral mononuclear entity with symmetric square‐planar geometry around the metal center. The complex exhibits an electrocatalytic behavior for proton reduction in DMF solvent using trifluoroacetic acid (TFA) as a proton source. Gas analysis under controlled electrocatalytic conditions during 4 h at a pool mercury working electrode showed a moderate production of dihydrogen. By combining experimental techniques to theoretical calculations, the results are analyzed and compared to those obtained for the previously reportedNiL complex in an effort to rationalize the influence of the metal center on the catalytic performance ofPdL to mediate hydrogen evolution. Abstract : How does the metal center influence the reaction mechanism and the catalytic properties for hydrogen production of thiosemicarbazone‐based complexes?